Multifunctional crop trait ontology for breeders' data: field book, annotation, data discovery and semantic enrichment of the literature - Shrestha, Rosemary; Arnaud, Elizabeth; Mauleon, Ramil; Senger, Martin; Davenport, Guy F.; Hancock, David; Morrison, Norman; Bruskiewich, Richard; McLaren, Graham (Oxford University Press, 2010)
Conclusions The controlled vocabularies of the CO are being used to curate several CGIAR centres' agronomic databases. The use of ontology terms to describe agronomic phenotypes and the accurate mapping of these descriptions into databases will be important steps in comparative phenotypic and genotypic studies across species and gene-discovery experiments